Pengembangan Bahan Cerita Tentang Pengorbanan Yesus Kristus di Kayu Salib dalam Pembelajaran Pendidikan Agama Kristen - 25, Lisbet Panggabean (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
Kata Kunci: Pengembangan, Bahan Cerita  Abstract: This study aims to development a product in the form of a story about the Sacrifice of Jesus Christ on the Cross on the subject of 5 th grade Christian Religious Education in the State Elementary School in Tarutung District 2019/2020 Academic Year. This research is a research and development (Research and Development RD). The results of the needs analysis showed that the respondents of the Trial study consisted of 20 PAK Teachers and several validations from theologians, linguists and method experts on the story method in learning Christian Religious Education with the material Sacrifice of Jesus Christ on the Cross. The results of the study concluded that the PAK teacher strongly agreed that the material about the Sacrifice of Jesus Christ on the Cross was taught using the story method, and strongly agreed that the story material was developed by the researcher. Because there is no reference (story) about the Sacrifice of Jesus Christ on the Cross. The results of the analysis of the researchers material product stories about the sacrifice of Jesus Christ.Keyword: Development, Story Material.